The Effectiveness Of The Character Class In The Matriculation Program On The Formation Of Discipline Among Grade X Students Of The 14Th At SMA Islam Athirah Bone - Mutmainnah, Mutmainnah (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2025)
This study aims to determine the effectiveness of the character class in the matriculation program on shaping positive discipline among Grade X students at SMA Islam Athirah Bone. Education is an essential aspect for students to develop intellectual abilities, and it also plays a significant role in character formation. SMA Islam Athirah Bone has implemented character education, particularly through the matriculation program, as an early effort to build positive discipline in new students, specifically those in Grade X. This research uses a descriptive quantitative approach, with data collected through a closed-ended questionnaire consisting of 36 statements covering five indicators of positive discipline and one indicator of the character class. The population of this study is all Grade X students at SMA Islam Athirah Bone, with a total sample of 84 respondents. The study was conducted at SMA Islam Athirah Bone. The results show that the average final score of the independent variable (character class) is 83.50%, while the dependent variable (positive discipline) scored 84.72%. Based on the score interpretation criteria, both results are categorized as very good. Therefore, it can be concluded that the character class in the matriculation program is effective in shaping positive discipline among Grade X students of the 14th cohort. This includes aspects such as punctuality, adherence to school rules, timely completion and submission of assignments, proper and respectful language use, and taking responsibility for acts of vandalismKeywords: Character Class, Matriculation Program, Formation of Discipline for Class X Students